2018
DOI: 10.1002/sscp.201800061
|View full text |Cite
|
Sign up to set email alerts
|

Determination of highly volatile compounds in fresh onion (Allium cepa L.) by room‐temperature enrichment headspace‐trap coupled to cryotrapping GC–MS

Abstract: Conventional headspace‐based analysis is not suitable for identifying volatile compounds in fresh onion (Allium cepa L.) because large amounts of water vapor could affect the determination of target compounds. A headspace‐trap was introduced to remove water vapor and keep the analytes in the trap tube. Additionally, the headspace‐trap method based on room‐temperature enrichment could prevent enzyme‐sensitive samples from denaturing to maintain the original flavor compositions of the samples. Moreover, the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…18). Besides dipropyl disulfide (35.45%), which was the most dominate sulfur compound identified in fresh onion, Liu et al (2018) [32] also reported a certain amount of 1-propanethiol, which was found to be abundant in A. cornutum (14.1%) and A. cepa L. in the current study. The second major compound present in A. cornutum (Table 1) was diisopropyl trisulfide, which was also reported to be the second most prominent compound present in A. cepa L., according to Ndoye Foe et al (2016) [17] and Teshika et al (2018) [33].…”
Section: Nosupporting
confidence: 60%
“…18). Besides dipropyl disulfide (35.45%), which was the most dominate sulfur compound identified in fresh onion, Liu et al (2018) [32] also reported a certain amount of 1-propanethiol, which was found to be abundant in A. cornutum (14.1%) and A. cepa L. in the current study. The second major compound present in A. cornutum (Table 1) was diisopropyl trisulfide, which was also reported to be the second most prominent compound present in A. cepa L., according to Ndoye Foe et al (2016) [17] and Teshika et al (2018) [33].…”
Section: Nosupporting
confidence: 60%
“…On the other hand, some compounds were in lower values or not detected such as 3,3-Thiobis-1-propene, and Dimethyl disulfide. Liu et al [38] reported that 1-propanethiol was the most abundant volatile compound in onion (14.1%) which was in agreement with the current study. The amount composition of volatile compounds is responsible for the biological activity and flavor [18,24].…”
Section: Volatile Compoundssupporting
confidence: 93%
“…33 Odorants identified in the blank were previously described in onions and mostly belonged to the following chemical classes: aldehydes, sulfur compounds, alcohols, ketones, and pyrazines. 22,34,35 The aldehydes mainly imparted a fatty, deep-fried, and green odor note, such as (E,E)-2,4-decadienal (No. 47, Table 1), whereas the sulfur compounds had alliaceous impressions, such as methyl propyl trisulfide (No.…”
Section: ■ Results and Discussionmentioning
confidence: 99%